Psychosocial factors and quality of life among flood victims in Malaysia - Marzuki, Najib Ahmad (GATR Enterprise, 2017)
Objective - The study seeks to determine the relationship between psychosocial factors, namely social support, impression management and emotional factors (stress, anxiety and depression), with quality of life among flood victims. The Conservation of Resources Stress Approach Model and The Social Support Deterioration Model suggest that quality of life is dependent upon these psychosocial factors. Methodology/Technique - The cross-sectional study examined 1300 flood victims in flood prone areas in Malaysia. The Multidimensional Scale of Perceived Social Support, The Bolino and Turnley Impression Management Scale and Depression, Anxiety and Stress Scale questionnaires were used to measure the psychosocial factors, while The WHO Quality of Life instrument was used to measure quality of life. The results were analysed using Pearson Correlations.Findings - The findings demonstrate that, in general, psychosocial factors are associated with quality of life. Social support dimensions and emotional factor dimensions were significantly correlated with quality of life. In addition, two dimensions of impression management were correlated with quality of life. The findings are consistent with the psychosocial theory that implies an overall relationship between the variables studied.Novelty – This study suggests that there is much to be done in terms of community flood education in Malaysia, as well as training for emergency aid providers to decrease the likelihood of negative effects of psychosocial factors on individuals' quality of life. A psychosocial support programme is recommended to enhance overall quality of life for flood victims. Type of Paper - Empirical